Radiotherapy plus a self-gelation powder encapsulating tRF5-GlyGCC inhibitor potentiates natural kill cell immunity to prevent hepatocellular carcinoma recurrence - Gong, Yihang; Zeng, Fanxin; Zhang, Feng; Liu, Xiaoquan; Li, Zhongheng; Chen, Wenjie; Liu, Haipeng; Li, Xin; Cheng, Yusheng; Zhang, Jian; Feng, Yeqian; Wu, Tiangen; et al. (Journal of nanobiotechnology, 2025)
Hepatocellular carcinoma (HCC) recurrence postresection represents a thorny problem in clinical practice, of which impaired natural killer (NK) cell cytotoxicity represents one of crucial causes. Apart from recurrence, hepatectomy-induced abdominal adhesion also poses huge clinical challenges such as abdominal pain, intestinal obstruction, and perforation. Evidence demonstrates that radiotherapy can upregulate NK group 2D ligand expression on tumor cells to enhance NK cell cytotoxicity, indicating its great potential of curbing HCC recurrence. Nevertheless, radiotherapy has also been disclosed to incur suppression on NK antitumor cell immunity. Herein, we reveal that glycocholic acid (GCA)/tRNA-derived fragment 5 (tRF5)-GlyGCC signaling axis is activated in mouse HCC model after radiotherapy, which dampens NK cell antitumor immunity to limit therapeutic efficacy. Mechanistically, tRF5-GlyGCC can interact with KDM6B to epigenetically upregulate Runx2 and then transcriptionally activate ITGBL1 and S100A9 expression in HCC cells, which further reduces NK cell cytotoxicity directly and attracts myeloid-derived suppressor cell (MDSC) to inhibit NK cell function indirectly, respectively. Therefore, radiotherapy plus targeting tRF5-GlyGCC may be an optimized postoperative adjuvant therapy against HCC recurrence. Then, a nanocomposite powder is designed for liver-localized delivery of tRF5-GlyGCC inhibitor. After sprayed to liver resection margin of mouse HCC model, this powder can rapidly form an in-situ Janus-adhesive hydrogel, which allows for sustained delivery of tRF5-GlyGCC inhibitor. Importantly, it can synergize with radiotherapy to potentiate NK cell antitumor immunity and prevent HCC recurrence postresection. Moreover, its application to surgical bed also effectively mitigates abdominal adhesion in a rat hepatectomy model. Altogether, our work develops a tRF5-GlyGCC-targeting nanocomposite power for sensitizing radiotherapy to thwart HCC recurrence and preventing abdominal adhesion.